Digitization of collecting mission data to enhance plant genetic resource management in maize (Zea mays) in India - PANDEY, ANJULA; SEMWAL, D P; BHANDARI, D C; SHARMA, SHASHI KANT (The Indian Journal of Agricultural Sciences, 2014)
The data gathered on germplasm collection of maize evidently showed is a preliminary attempt on digitization of collecting mission data of maize genetic resources to enhance its use in plant genetic resource management in maize in India through quality passport data, eco-geographic location, availability of germplasm site description, geographic coordinates for crop improvement programme. Identification of collection sites located in distribution maps would allow: pinpointing of directed collection plans in under represented and identified sites that are rich in landraces/ trait-specific diversity. Since these sites are highly vulnerable to genetic erosion due to spread of hybrids/ genetically modified crops (GM), such areas need to be given special attention in genetic resource management. Broadly all maize growing areas have been surveyed in the past and diversity augmented from different parts of the country. However, based on gaps identified in the genebank holdings of trait specific germplasm and unique material needs to be augmented. Grouping of local cultivars/ landraces of maize based on geographical distribution, morphology, field and molecular characterization is a major challenge that needs special address by the maize breeders and users.